"Lidocaine anaphylaxis after epidural anesthesia for cesarean section " - Setayesh AR (Acta Medica Iranica, 2001)
Allergic reaction to local anesthetics is very rare and most of the reported cases are due to ester local anesthetics. This case presents a parturient who experienced cardiac arrest due to hypersensitivity reaction to lidocaine after epidural injection for cesrarean section.